2009
DOI: 10.4049/jimmunol.0803912
|View full text |Cite
|
Sign up to set email alerts
|

The Coding ECP 434(G>C) Gene Polymorphism Determines the Cytotoxicity of ECP but Has Minor Effects on Fibroblast-Mediated Gel Contraction and No Effect on RNase Activity

Abstract: Eosinophil cationic protein (ECP) is a secretory protein of the eosinophil granulocyte, a cell involved in innate immunity. Functional studies have implicated ECP in numerous processes, such as tissue remodeling in allergic inflammation and cytotoxicity toward a variety of pathogens. Recent genetic studies have suggested that the ECP 434(G>C) polymorphism resulting in an arg97thr substitution would alter the function of ECP in vivo. Functional (in vitro) studies of ECP up until now have either been cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…Site-directed mutagenesis studies identifi ed the main critical residues exposed at the protein surface involved in membrane lysis and cytotoxicity (Carreras et al , 2003 ;Torrent et al , 2007 ;Singh and Batra , 2011 ). Additionally, complementary studies on the protein native posttranslational forms and comparison of polymorphism variants highlighted the contribution of glycosylation on the protein cytotoxic power (Trulson et al , 2007 ;Rubin et al , 2009 ;Woschnagg et al , 2009 ). In the following section, we detail the current knowledge on ECP antimicrobial properties.…”
Section: The Eosinophil Cationic Protein (Ecp) In Host Defencementioning
confidence: 99%
“…Site-directed mutagenesis studies identifi ed the main critical residues exposed at the protein surface involved in membrane lysis and cytotoxicity (Carreras et al , 2003 ;Torrent et al , 2007 ;Singh and Batra , 2011 ). Additionally, complementary studies on the protein native posttranslational forms and comparison of polymorphism variants highlighted the contribution of glycosylation on the protein cytotoxic power (Trulson et al , 2007 ;Rubin et al , 2009 ;Woschnagg et al , 2009 ). In the following section, we detail the current knowledge on ECP antimicrobial properties.…”
Section: The Eosinophil Cationic Protein (Ecp) In Host Defencementioning
confidence: 99%
“…Eosinophil samples (each containing 10 ng of ECP) or 0.5 g of purified ECP (see Ref. 16 for details on ECP purification) were added to the wells and the arrays were incubated in 4°C overnight with mild shaking.…”
Section: Seldi-tof Ms Affinity Capture Assaymentioning
confidence: 99%
“…ECP (HMW-ECP) and one low m.w. ECP (LMW-ECP) pool (16). The two ECP pools were characterized by SELDI-TOF MS. Fig.…”
Section: Cytotoxicity Of Purified Ecpmentioning
confidence: 99%
“…Due to G>C sub sti tu tion, the co don for the ami no acid ar gi ni ne is chan ged in the co don for threo ni ne, whi ch lea ds to the chan ge in Ar g97Thr in the ECP pro tein. The consequen ce of the chan ge in ami no acid struc tu re is al te ra tion of bio lo gi cal ac ti vi ty of the ECP mo le cule be cau se Ar g97 is im por ta nt for the cyto toxic acti vi ty of ECP (19,20). The sub sti tu tion of ar gi ni ne at po si tion 97 wi th threo ni ne al lows the for ma tion of a new, four th glyco syla tion si te at po si tion 95 (EC-P 95Asn ), and en han ced glyco syla tion of ECP pro tein dec rea ses its cyto toxic ac ti vi ty.…”
Section: Rna Se3 Po Lymor Phis Msmentioning
confidence: 99%
“…The sub sti tu tion of ar gi ni ne at po si tion 97 wi th threo ni ne al lows the for ma tion of a new, four th glyco syla tion si te at po si tion 95 (EC-P 95Asn ), and en han ced glyco syla tion of ECP pro tein dec rea ses its cyto toxic ac ti vi ty. Stu dies of re combi na nt ECP 97Thr have showed that, af ter deg lycosyla tion, it be co mes cyto toxi cal ly ac ti ve li ke EC-P 97Arg (20). Pa ra si ta ry in fec tio ns, as thma and ma ligna nt di sea ses are on ly so me pat ho lo gi cal con di tions wi th ECP in vol ve me nt in their pat ho mec ha nisms so that di sea se out co me is as so cia ted wi th ECP phe no type or ge no type.…”
Section: Rna Se3 Po Lymor Phis Msmentioning
confidence: 99%